HMGB1 lactylation drives neutrophil extracellular trap formation in lactate-induced acute kidney injury - Zhu, Li; Zheng, Qiang; Liu, Xiaodong; Ding, Hao; Ma, Mengqing; Bao, Jiaxin; Cai, Yawen; Cao, Changchun (Frontiers in Immunology, 2025)
RationaleAcute kidney injury (AKI) is a clinical syndrome associated with a multitude of conditions. Although renal replacement therapy (RRT) remains the cornerstone of treatment for advanced AKI, its implementation can potentially pose risks and may not be readily accessible across all healthcare settings and regions. Elevated lactate levels are implicated in sepsis-induced AKI; however, it remains unclear whether increased lactate directly induces AKI or elucidates the underlying mechanisms.MethodsFor human, the measurement of lactate in arterial blood gas is performed using the direct determination of L-lactate through an electrode oxidation method by a blood gas analyzer. For mice, enzyme-linked immunosorbent assay (ELISA) kits were employed to quantify the concentrations of lactate and AKI biomarkers in blood and cell supernatant. The mouse model of AKI was performed with a single intraperitoneal (i.p.) administration of lactate (30 mg/kg) and low-dose LPS (2 mg/kg) for 24 h. Proteomic analysis was conducted to identify lactylated proteins in kidney tissues. Techniques such as, immunoprecipitation, western blotting and immunofluorescence were used to evaluate the levels of HMGB1 lactylation, neutrophil extracellular traps (NETs)and to assess related molecular signaling pathways.Main resultsOur findings indicate that lactate serves as an independent predictor of AKI in patients with acute decompensated heart failure (ADHF). We observed that co-administration of lactate with low-dose lipopolysaccharide (LPS) resulted in lactate overproduction, which subsequently elevated serum levels of creatinine (Cre) and blood urea nitrogen (BUN). Furthermore, the combined application of lactate and low-dose LPS was shown to provoke HMGB1 lactylation within renal tissues. Notably, pretreatment with HMGB1 small interfering RNA (siRNA) effectively diminished lactate-mediated HMGB1 lactylation and alleviated the severity of AKI. Additionally, lactate accumulation was found to enhance the expression levels of NETs in the bloodstream, with circulating NETs levels positively correlating with HMGB1 lactylation. Importantly, pre-administration of HMGB1 inhibitors (glycyrrhizin) or lactate dehydrogenase A (LDH-A) inhibitors (oxamate) reversed the upregulation of NETs induced by lactate and low-dose LPS in both the blood and polymorphonuclear neutrophils (PMNs) cell supernatant, thereby ameliorating AKI associated with lactate accumulation.ConclusionsThese findings illuminate the role of lactate-mediated HMGB1 lactylation in inducing AKI in mice through the activation of the HMGB1-NETs signaling pathway.